ECONOMIC STRATEGIES IN GERMANY: CHALLENGES AND OPPURTUNITIES IN DEVELOPING COMPETITIVE ADVANTAGE - Machfud; Rizky Febri Anggi; Handayni; Munarisma; Liza Maulia (RADJA PUBLIKA, 2023)
Germany has long been recognized as one of the world's strong and innovative economies. Germany's economic success is not only supported by a strong industrial sector, but also by an effective economic strategy. However, like any other country, Germany also faces various challenges in maintaining its economic growth and sustainability. The purpose of this study is to analyze the strategies that have been implemented by the German government and companies in the face of current economic challenges. The method used in this journal is descriptive qualitative research. Descriptive qualitative research aims to gain a deep understanding of the phenomenon under study and describe it in detail. This method allows the author to collect more detailed data and understand the context behind Germany's economic problems.